PROFITABILITAS MEMODERASI FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Sara Lumbantoruan, (2020)
This research is a quantitative study that aims to determine whether profitability is able to moderate the factors that influence the disclosure of Corporate Social Responsibility (CSR) and also the effect of tax aggressiveness, company size and liquidity on CSR disclosures. This study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016 - 2018 as a population. The sanpel selection technique uses a purposive sampling method and samples obtained by 67 companies from the manufacturing sector. Testing the hypothesis in this study using Multiple Regression Analysis using SPSS software version 25 and Moderated Regression Analysis (MRA) with a significance level of 5%. The results of this study indicate that: (1) tax aggressiveness using the book tax difference (BTD) proxy has a negative effect on CSR disclosure, (2) company size has a positive effect on CSR disclosure, (3) liquidity using the current ratio (CR) proxy has a negative effect on CSR disclosure, (4) profitability is not able to strengthen or weaken the relationship between tax aggressiveness on CSR disclosure, (5) profitability is not able to strengthen or weaken the relationship of company size to CSR disclosure, (6) profitability is not able to strengthen or weaken the relationship of liquidity to CSR disclosure .